UTILIZATION OF BANANA HUMP (Musa paradisiaca L) IN MAKING EDIBLE FILM WITH ADDITIONAL CARAGENAN - dian rizky afriani; Indang Dewata; Mawardi Mawardi; Hary Sanjaya (Universitas Negeri Padang, 2021)
The purpose of the study was to determine the optimum conditions for the effect of adding carrageenan to edible films made from banana weevil starch on the chemical structure, mechanical properties and physical properties, and to compare the mechanical properties of edible films. This research was conducted by adding polyethylene glycol with a concentration of 4% and varying carrageenan with a concentration of 0%; 0.5%; 1%; 1.5%; and 2%. The optimum conditions for the addition of carrageenan were found at a concentration of 1%, with a tensile strength value of 28.76 Mpa, and an elasticity value of 2311.83 Mpa. As for the physical properties, namely thickness and biodegradation, the value increased with increasing carrageenan concentration. Spectra of edible film without carrageenan and edible film with the addition of OH at the addition of OH at wave numbers 3500 – 3200 cm-1, CH at wave numbers 3000 – 2800 cm-1, and CO at wave numbers 1085 – 1050 cm -1